Clinical and genetic determinants of ovarian metastases from colorectal cancer. Issue 7 (22nd November 2016) - Ganesh, Karuna; Shah, Ronak H.; Vakiani, Efsevia; Nash, Garrett M.; Skottowe, Hugh P.; Yaeger, Rona; Cercek, Andrea; Lincoln, Anne; Tran, Christina; Segal, Neil H.; Reidy, Diane L.; Varghese, Anna; et al.
Abstract : BACKGROUND: Ovarian metastases from colorectal cancer (OM‐CRC) often are unresponsive to chemotherapy and are associated with poor survival. To the authors' knowledge, the clinicopathologic and genomic predictors of OM‐CRC are poorly characterized and optimal clinical management remains unclear. METHODS: Women with a histopathological diagnosis of OM‐CRC who were treated at Memorial Sloan Kettering Cancer Center from 1999 to 2015 were identified. Next‐generation somatic mutation profiling (Memorial Sloan Kettering‐Integrated Mutation Profiling of Actionable Cancer Targets [MSK‐IMPACT]) was performed on 38 OM‐CRC cases, including 21 matched tumor pairs/trios. Regression models were used to analyze variables associated with progression‐free survival and overall survival (OS). RESULTS: Kirsten Rat Sarcoma Viral Oncogene Homolog ( KRAS ), SMAD family member 4 ( SMAD4 ), and neurotrophic receptor tyrosine kinase 1 ( NTRK1 ) mutations were more frequent in cases of OM‐CRC than in instances of CRC occurring without OM. SMAD4 and lysine methyltransferase 2D ( KMT2D ) mutations were associated with reduced OS. Matched multisite tumor sequencing did not identify OM‐specific genomic alterations. Of the 195 patients who underwent oophorectomy for OM‐CRC (median age, 49 years with a progression‐free survival of 9.4 months and an OS of 23 months from oophorectomy), 76% had extraovarian metastasis (EOM). In multivariable analysis, residual disease after surgery (R2 resection) was associated with worse survival. Patients with EOM were less likely to achieve R0/R1 surgical resection status (complete macroscopic resection without clinical/radiological evidence of disease) (48% vs 94%). However, if R0/R1 resection status was achieved, both patients with (35.9 months vs 12 months) and without (43.2 months vs 14.5 months) EOM were found to have better OS. Among 114 patients with R0/R1 resection status, 23 (20%) had no disease recurrence, including 10 patients (9%) with > 3 years of follow‐up. CONCLUSIONS: Loss‐of‐function alterations in SMAD4 are frequent and predictive of worse survival in patients with OM‐CRC. Similar to oligometastatic CRC to the lung or liver, surgical resection of OM‐CRC is associated with a better outcome only if all macroscopic metastatic disease is resected. Cancer 2017;123:1134–1143. © 2016 American Cancer Society . Abstract : The results of this large retrospective study of patients with ovarian metastases from colorectal cancer demonstrate that patients who undergo complete surgical resection of all macroscopic metastatic disease have a better prognosis than those who undergo incomplete surgical resection. In addition, the authors identify tumor mutations specifically associated with ovarian metastases and with poor survival, thus laying the foundation for future genetic risk stratification of candidates for oophorectomy.